PERCEPTIONS OF POPULISM: ANALYSIS OF MEDIA DISCOURSE IN LATVIA - Balcere, Ilze (Baltic Journal of Political Science, 2013)
This article intends to analyze how the term ‘populism’ is used in the Latvian public discourse, by examining the content of the largest daily newspaper “Diena” in three different time periods. As it emerges from the analysis, populism has gained a different meaning in the daily usage in contrast with the more established understanding conveyed by the academic literature. In the media, populism is used to a refer to wide range of politicians, different parties and policy initiatives from diverse ideological spectra. Most often, however, populism is employed to describe rhetorics or communication style whose primary goal is to attract public attention.